2006
DOI: 10.1590/s0104-56872006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Provas de nomeação e imitação como instrumentos de diagnóstico do transtorno fonológico

Abstract: Background: phonological disorder. Aim: to verify the association between the phonological performance in picture naming and imitation tasks, assessing the occurrence of phonological processes and using the severity indexes of Percentage of Correct Consonants and Phonological Density Index. Method: participants of this research were 50 phonologically disordered children, with no history of prior speech-language therapy and with ages between 4:0 and 12 years. Results: The analysis of the phonological processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
34

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 20 publications
1
17
0
34
Order By: Relevance
“…highlight the gliding of liquids phonemes, cluster reduction and final consonant deletion , which are also highlighted in other studies [18][19][20][21] . These processes have a higher prevalence in children with disorders in phonological abilities.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…highlight the gliding of liquids phonemes, cluster reduction and final consonant deletion , which are also highlighted in other studies [18][19][20][21] . These processes have a higher prevalence in children with disorders in phonological abilities.…”
Section: Resultssupporting
confidence: 75%
“…Studies that investigated the abilities and disorders of language in children, who stutter, indicated that this group compared with those who do not stutter, had presented lower scores on several indices of receptive and expressive language [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Methodsmentioning
confidence: 99%
“…Data from this study showed that in G2 there was a greater number of children classified as inconsistent, suggesting a probable involvement of phonological programming, resulting in *Significant values (p<0.05) -Spearman correlation coefficient Note: # Naming = picture naming task; ## Imitation = imitation of words; PCC-R = percentage of consonants correct revised; PDI = phonological density index; RSI = relative substitution index; ROI = relative omission index; RDI = relative distortion index; SII = speech inconsistency index a difficulty cognitive-linguistic representation of phonological rules of the language (15) . Is worth mentioning that the comparison between the evidence of imitation and naming tasks indicated no differences for the indices studied, which demonstrates the effectiveness of the application of these indices in any speech sample (29) . The correlations between the scores on both tests also suggest that these indicators remained an association of values in both tests.…”
Section: Discussionmentioning
confidence: 64%
“…Esta diferença entre o fonema nas duas posições dentro da sílaba foi observada em um estudo anterior (25) . Crianças com transtorno fonológico apresentam como processos mais ocorrentes a simplificação de líquida e a simplificação da consoante final (26)(27) . Este dado encontrado sobre crianças em desenvolvimento fonológico típico ajuda no tratamento de crianças com transtorno fonológico visto que, em alguns estudos, opta-se por iniciar o trabalho terapêutico com sons mais complexos do sistema fonológico das crianças para que se atinja um efeito maior de generalização (28)(29)(30) .…”
Section: Discussionunclassified